Cooling of microelectronic and nanoelectronic equipment : advances and emerging research - Iyengar, Madhusudan editor; Geisler, Karl J. L editor; Sammakia, Bahgat, 1952- editor (New Jersey : World Scientific, 2015)
Includes bibliographical references and index.